The genesis of the writings of St. Faustina Kowalska and Alicja Lenczewska - Rachwalik, Walter (Studia Teologiczne Białystok Drohiczyn Łomża, 2021)
The group of Polish mystics includes St. Sister Faustina Kowalska (1905-1938) and Alicja Lenczewska (1934-2012). After their death, with the consent of the Church’s Pastors, their spiritual records were published, in which they recorded their own supernatural experiences and God’s teachings to His followers. The Diary, the Testimony and the Word of Instruction have been recognized as pearls of mystical scriptures.